Implementation of Interactive Nurses Effective Communication Guidelines - Pipit Puspita Dewi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Patient safety is a system whereby the hospital keeps the patient's care safer by preventing injuries caused by errors resulting from taking an action or not taking appropriate action. One component of patient safety is effective communication. Improving effective communication is one way of achieving patient safety according to patient safety standards. This study aims to analyze how the implementation of effective communication guidelines for nurses. This research is a mix method with a cross-sectional design. Quantitative data to see the knowledge, abilities, and compliance of nurses selected by simple random sampling. Qualitative data were obtained by conducting a deep interview to the head of the inpatient ward, emergency department supervision, and supervision of the nursing manager. The number of samples in this study was 37 in-patient nurses, 6 ward heads and 2 supervisors. The research instrument used is the questionnaire and checklist. Data analysis using Spearman test. This study found that there is a relationship between nurse knowledge, abilities, and compliance in the implementation of effective communication guidelines and there are obstacles in the process of implementing effective communication guidelines.